Challenges on the Inheritance of traditional wool felt making skills in Zhaotong Dashanbao Loop, China - Huang, yan; Shaari, Nazlina; Zainal Abidin, Sazrinee; Liu, Mingquan (SHPMedia Sdn Bhd, 2024)
The Dashanbao Loop is dominated by high mountainous and hilly landscapes and is located on the plateau where the Jinsha River meets the Nilan River in the western Zhaoyang District of Zhaotong City, Yunnan Province. There is a big temperature difference between day and night here. To keep out the cold, people will use wool to make daily necessities such as cloaks, mattresses and insoles. This material can keep moisture-proof and warm, so the traditional hand-made felt technology handed down from generation to generation is still retained. These traditional crafts not only show unique cultural value, but also become valuable local cultural heritage. However, today's globalization and the development of modern technology have brought unprecedented challenges to these traditional processes. The study systematically collects and organizes data on the traditional wool felt making techniques of the Dashanbao Loop from the perspective of intangible cultural heritage preservation, using both observation and interview methods. The study conducted field investigation and interviews with wool felt makers, and through the data obtained analyzed the transmission dilemmas faced by these traditional skills was analyzed, focusing on the challenges to their transmission and their potential solutions. According to the data, these traditional products have major challenges in these aspects: the product categories are not rich and rough, the inheritance method is single, the environment changes and the inheritor's income is low. In order to solve these problems, it is suggested to break through the existing product categories, diversify inheritance methods, improve the inheritance environment and improve the treatment of inheritors, which is more conducive to the inheritance and sustainable development of traditional crafts. © 2024, SHPMedia Sdn Bhd. All rights reserved.